Knockout of the polysialyltransferases ST8SiaII and ST8SiaIV leads to a dilatation of rete testis during postnatal development - Humpfle, Luisa; Hachem, Nadim E.; Simon, Peter; Weinhold, Birgit; Galuska, Sebastian P.; Middendorff, Ralf (Frontiers in Physiology, 2023)
Polysialic acid (polySia) is a carbohydrate polymer that modulates several cellular processes, such as migration, proliferation and differentiation processes. In the brain, its essential impact during postnatal development is well known. However, in most other polySia positive organs, only its localization has been described so far. For instance, in the murine epididymis, smooth muscle cells of the epididymal duct are polysialylated during the first two weeks of postnatal development. To understand the role of polySia during the development of the epididymis, the consequences of its loss were investigated in postnatal polySia knockout mice. As expected, no polysialylation was visible in the absence of the polysialyltransferases ST8SiaII and ST8SiaIV. Interestingly, cGMP-dependent protein kinase I (PGK1), which is essentially involved in smooth muscle cell relaxation, was not detectable in peritubular smooth muscle cells when tissue sections of polySia knockout mice were analyzed by immunohistochemistry. In contrast to this signaling molecule, the structural proteins smooth muscle actin (SMA) and calponin were expressed. As shown before, in the duct system of the testis, even the expression of these structural proteins was impaired due to the loss of polySia. We now found that the rete testis, connecting the duct system of the testis and epididymis, was extensively dilated. The obtained data suggest that less differentiated smooth muscle cells of the testis and epididymis result in their disturbed contractility and thus, fluid transport within the duct system visible in the enlarged rete testis.